2022
DOI: 10.1039/d2cy00969b
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of dependence between the deoxygenation activity and metal–support interface

Abstract: The nature of the active sites responsible for the cleavage of C-O bonds in biomass-derived phenolic compounds has been a subject of speculation. Although HDO activity has long been attributed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The interaction of a noble metal with a reducible metal oxide can generate new highly active sites at the interface that, in some cases, account for most or all of the HDO activity. In some instances, it can be challenging to distinguish these highly active sites located at the metal–support interface from surface-promoted effects created by hydrogen spillover from the metal . To maximize SDO rates and design a better catalyst system, it is important to identify the active sites responsible for this chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of a noble metal with a reducible metal oxide can generate new highly active sites at the interface that, in some cases, account for most or all of the HDO activity. In some instances, it can be challenging to distinguish these highly active sites located at the metal–support interface from surface-promoted effects created by hydrogen spillover from the metal . To maximize SDO rates and design a better catalyst system, it is important to identify the active sites responsible for this chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[8,[14][15][16][17][18] It is generally believed that the interfacial perimeter site between metal and oxide plays a crucial role in such improved performance. [17,[19][20][21][22][23][24][25][26][27] Newman et al reported higher benzene selectivity during HDO of phenol on Ru/TiO 2 catalysts with small Ru size (1.5 nm) than large Ru size (33 nm), and ascribed this difference to the increased Ru-TiO 2 interfacial perimeter sites for smaller Ru size. [27] Lately, direct correlation between the deoxygenation activity and interfacial perimeter site was reported on Pt/Nb 2 O 5 and Ru/TiO 2 catalysts by assuming that the number of perimeter site is related with the metal particle size.…”
Section: Importance Of Perimeter Site At Metal/oxide Interface For Hdomentioning
confidence: 99%
“…[27] Lately, direct correlation between the deoxygenation activity and interfacial perimeter site was reported on Pt/Nb 2 O 5 and Ru/TiO 2 catalysts by assuming that the number of perimeter site is related with the metal particle size. [26,28] Clearly, these works highlighted the importance of metal/oxide interfacial perimeter site in DDO of phenolics. However, these works ignored the reduced metal particle size may also contribute to the improved DDO activity, since the DDO reaction is structure sensitive and its activity is strongly dependent on the metal particle size.…”
Section: Importance Of Perimeter Site At Metal/oxide Interface For Hdomentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the HDO of phenolics has been explored on various types of catalysts. [16][17][18][19][20][21][22][23] Among them, Ni-based catalysts have been intensively investigated, [24][25][26][27][28][29][30][31][32][33] since Ni shows excellent ability to dissociate H 2 and is much cheaper than other typical noble metal based hydrogenation catalysts. However, monometallic Ni catalysts exhibit at low temperatures a low deoxygenation activity but high hydrogenation activity, resulting in saturation of the phenyl ring, and at high temperatures a hydrogenolysis activity toward the C-C bond, resulting in a high methane yield and lowered aromatic selectivity.…”
Section: Introductionmentioning
confidence: 99%